Proposed SOP Design For The Implementation of K3 to Meet The Requirements of ISO 45001:2018 Clause 6.1 in The Production Division at PT Mega Jaya Logam - Nusaibah Nusaibah; Sri Widaningrum; Sheila Amalia Salma (Syntax Literate, 2022)
PT XYZ is a metal casting industry company, where in the production process there are several potential hazards. The efforts made by the company to overcome these potential hazards are to provide PPE facilities to workers. However, the workers lack of self-awareness of OHS makes them not comply with the use of PPE. Therefore, work accidents still occur in the company. The methods used in the design proposal stage are FMEA and FTA. FMEA and FTA are failure analysis methods, FMEA can also be used to assess failures that occur. The stages of the two methods are integrated to then create a process of hazard identification, risk assessment, and control. The proposed design is in the form of a Risk Control SOP. The purpose of the Risk Control SOP is to identify what hazards occur in the production process and assess the level of risk, so that the company can provide appropriate controls for existing hazards. The SOP was made to fulfill the requirements contained in Clause 6.1 of ISO 45001: 2018 and PP No. 50 of 2012 concerning OHSMS. With the Risk Control SOP, it is hoped that it can assist the company in improving the company's OHSMS and the company can achieve zero accidents.